(3JMaI GdCfGe aj aVGFd GdTGes - (3CMeO Hf eMeO, GdHUQhj, TeS GdOjf CHh GdYHGS , GHf ,J (B1015 (3g` s
(3ChdgG (B:s
(3hHYO agPg ChQGb GPcQ ajgG Ef TGA Gddg JYGdi eGJjSQ GdEWdGY Ydjg hSgd GdhUhd Edjg , ef cJH JhGQjN GdESdGe s
(3BNQgG (B:s
(3Ke JgH QjM ef Gdjef aJbHV CQhGM GdeDefjf , hHYOg GdSGYg Ydi TQGQ GdNdb , hGddg SHMGfg hJYGdi CYde s
(3GfXQ CjkVG Qbe (B148 (3JGQjNs
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs